EMPLOYEE ENGAGEMENT ON WORK MOTIVATION AND ITS IMPACT ON INTENT TO LEAVE AT BUKIT RAYA SEKAWAN MINING COMPANY - Yudhistira Anugerah Pratama; Louisiani Mansoni Isnajati (PT. Altin Riset Publishing, 2026)
Employee engagement plays a crucial role in organizational success, influencing motivation, job satisfaction, and turnover intention. This study examines the relationship between employee engagement, work motivation, and turnover intention at Bukit Raya Sekawan Mining Company, addressing gaps in research within the mining sector. Using a quantitative approach with path analysis, data were collected from employees through surveys and observations, supplemented by secondary sources. Findings indicate that most employees perceive their engagement as appropriate to very strong, and the majority report high levels of work motivation. Turnover intention appears relatively low, with only a small proportion of employees showing a strong inclination to leave. The analysis reveals that employee engagement has a substantial impact on work motivation and turnover intention. Work motivation also directly affects turnover intention, underscoring its role in employee retention. Moreover, engagement indirectly influences turnover intention through motivation, reinforcing its overall effect. These results highlight the importance of fostering a supportive work environment, improving career development opportunities, and enhancing compensation to strengthen engagement and motivation. Future studies should explore additional factors such as leadership, organizational culture, and work-life balance to provide comprehensive understanding of employee behavior in the mining industry.